Denervation of pulmonary trunk and pulmonary orifice in patients with surgically corrected mitral valve disease against high pulmonary hypertension - N. A. Trofimov; A. P. Medvedev; A. G. Dragunov; V. E. Babokin; A. V. Nikol'skiy; T. N. Mizurova; M. V. Gartfelder; A. V. Orlova (Alʹmanah Kliničeskoj Mediciny, 2017)
Aim: To study efficacy and safety of denervation of the trunk and pulmonary arteries (PADN procedure) in patients with surgical correction of the mitral valve against a high degree of pulmonary hypertension compared to those of the isolated correction of mitral valve disease.Materials and methods: Placement of a mechanical mitral valve prosthesis and radiofrequency ablation Maze IV with Atri Cure ablator was performed in 39 patients with a mitral valve disease and high pulmonary hypertension (> 40 mm Hg) and atrial fibrillation. From those, 8 patients (main group) had additional circular denervation of the ganglionic plexus of the pulmonary trunk and orifice (PADN) with a radiofrequency bipolar Atri Cure ablator under the control of transmurality.Results: All patients who had underwent surgery showed positive changes of the echocardiographic parameters, such as a decrease in the heart cavities sizes, degree of pulmonary hypertension, and an improvement in the systolic function of the left ventricle. There were no deaths, as well as specific complications related to the PADN procedure. In the main group of patients (n = 8), pulmonary hypertension decreased from 56.3 ± 5.4 mm Hg to 23.4 ± 2.7 mm Hg at day 1, to 24.3 ± 3.1 mm Hg at day 7, and to 23.7 ± 3.8 mm Hg at 1 month after the PADN procedure. At day 1, the target levels of pulmonary hypertension were achieved in 87.5% (7/8) of patients in the main study group and in 25.8% (8/31) of patients in the control group (p = 0.001). At day 7, the corresponding values were 75% (6/8) and 32.3% (10/31), respectively. Better results in the main study group were observed throughout the whole follow-up period (up to 2 months).Conclusion: The circular PADN procedure using a radio frequency bipolar ablator under the control of transmurality is an effective and safe method to correct a high-degree pulmonary hypertension. Further studies on the effectiveness of this procedure in larger patient numbers and assessment of long-term results are necessary.